Who pays for clean air, and why?: Analyzing the impact of resource, planned behavior, and government/policy factors on the multidimensional willingness to pay for reducing the particulate matter - Jeon, Sehyeok; Kim, Seoyong; Kim, Sohee (Heliyon, 2024)
This study aimed to explore the determinants of willingness to pay for fine particulate matter reduction. Previous studies were mostly based on simple causal models, with few or similar predictors affecting a single dimension of willingness to pay. This study adopted a multidimensional model, dividing willingness to pay into three categories: cost burden, benefit to the community and benefit to specific groups. The independent variables were resources, planned behavior, and government/policy factors, with a total of 12 variables. The analysis showed that, first, the determinant structure varied across the dimensions of willingness to pay. Second, facility resources, information, personal norms, social norms, perceived control, trust in government, policy satisfaction, policy preference, and policy knowledge had significant positive effects on willingness to pay. Third, policy satisfaction and social norms had high explanatory power for willingness to pay for cost burden; policy preference and personal norms for benefit to community; and policy knowledge, policy preference, and perceived control for benefit to specific groups.
Keywords: Government/policy factor; Multidimensionality of willingness to pay; PM (particulate matter); Resource theory; Theory of planned behavior